Polyphenols composition, antioxidant and antimicrobial properties of Pinus sylvestris L. shoots extracts depending on different drying methods - Dziedziński, Marcin; Kobus-Cisowska, Joanna; Powałowska, Daria Szymanowska-; Szablewska, Kinga Stuper-; Baranowska, Marlena (Emirates Journal of Food and Agriculture, 2020)
Scots pine (Pinus sylvestris L.) shoots have been increasingly commonly used as functional food or its component, the shoots contain various active components, unknown from other raw materials. The objective of the study was to assess the influence of the drying method on the content of bioactive compounds and antioxidative and antimicrobial activity of pine shoots. It was demonstrated that freeze drying (PSL), vacuum drying (PSP) and natural drying (PSN) have significant impact on the physicochemical properties, content of bioactive compounds and antioxidative activity of the prepared ethanol-water extracts. The content of the studied compounds varied significantly in the tested shoots. In spectrophotometric testing the highest total flavonoid content was demonstrated in the PSP sample, at 5.51 mg quercetin/g dw. On the other hand, the reducing capacity was as follows: PSN>PSP>PSL in the range from 13.4 to 5.73 mg gallic acid/g dw. However in assay conducted using HPLC methods the highest content of polyphenols characterized extract from freeze-dried raw material (9151.15 µg/g), followed by vacuum-dried (8264.57 µg/g), and the lowest content of phenolic compounds was found in convection-dried shoots (7621.76 µg/g). The studied extracts demonstrated antioxidative properties, both in ferric reducing antioxidant power assay (FRAP) as well as in free radical quenching measurement (DPPH). All of the studied extracts demonstrated antimicrobial and fungicidal properties, and they were particularly efficient in the case of gram-negative bacteria.